2017
DOI: 10.3390/app7070683
|View full text |Cite
|
Sign up to set email alerts
|

Data Mining Approaches for Landslide Susceptibility Mapping in Umyeonsan, Seoul, South Korea

Abstract: The application of data mining models has become increasingly popular in recent years in assessments of a variety of natural hazards such as landslides and floods. Data mining techniques are useful for understanding the relationships between events and their influencing variables. Because landslides are influenced by a combination of factors including geomorphological and meteorological factors, data mining techniques are helpful in elucidating the mechanisms by which these complex factors affect landslide eve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
33
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 44 publications
2
33
0
Order By: Relevance
“…The Receiver Operating Characteristics (ROC) curve [58] is mainly used for assessing accuracy. It has been widely used in works involving land cover change, disease risk and species distribution studies [59], landslide susceptibility mapping [19,60], groundwater potential mapping [6], and for assessing groundwater vulnerability [61]. In this work, ROC assesses the spatial coincidence between the true event and predicts the probability of the model [59].…”
Section: Accuracy Assessmentmentioning
confidence: 99%
“…The Receiver Operating Characteristics (ROC) curve [58] is mainly used for assessing accuracy. It has been widely used in works involving land cover change, disease risk and species distribution studies [59], landslide susceptibility mapping [19,60], groundwater potential mapping [6], and for assessing groundwater vulnerability [61]. In this work, ROC assesses the spatial coincidence between the true event and predicts the probability of the model [59].…”
Section: Accuracy Assessmentmentioning
confidence: 99%
“…The first and second papers, authored by Lee, S., Lee, M., Jung, H. [1] and Oh, H., Lee, S. [2], applied GIS and various machine learning algorithms such as artificial neural networks, support vector machines, and boosted tress to map landslide susceptibility. The third paper, authored by Lee, S., Lee, S., Song, W., Lee, M. [3], applied GIS with artificial neural networks to map potential marten and leopard habitats.…”
Section: Applications Of Artificial Neural Network In Geoinformaticsmentioning
confidence: 99%
“…In bivariate statistical analysis, the weights of the landslide conditioning factors are assigned based on landslide density using different methods-including frequency ratio (FR) [13,15,[20][21][22], the information content model (ICM) [23,24], weight of evidence (WoE) [16], certainty factors (CF) [25], favorability functions (FF) [26], and the likelihood ratio model (LRM) [27]. The multivariate statistical methods evaluate the combined relationship between a dependent variable (landslide occurrence) and a series of independent variables (landslide controlling factors), and the most popular methods to analyze the resulting matrix include logistic regression (LR) [6,13,[28][29][30][31][32][33], discriminant analysis (DA) [34,35], random forest (RF) [36][37][38] and active learning statistical analysis, such as the artificial neural networks (ANNs) [3,6,[39][40][41][42].Physically based methods, such as deterministic techniques, are based on mathematical modeling of the physical mechanisms controlling slope failure [43][44][45][46][47][48][49]. However, it is reported that the methods are only applicable over large areas when the geological and geomorphological conditions are fairly homogeneous and the landslide types are simple [17].Moreover, several studies have used two or more models to produce landslide susceptibi...…”
mentioning
confidence: 99%